PENINGKATAN PENJARIAN RECORDER SOPRAN MENGGUNAKAN MEDIA VISUAL PADA SISWA KELAS VIIB SMPN 7 SUNGAI RAYA - Ening Juwita Meiyana; Ismunandar Ismunandar; Asfar Muniir (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2018)
Abstact This study aimed to describe the implementation and outcomes that use visual media fingering for competence learning to play music in class VIII B SMPN 7 Sungai Raya. The method used in this research is action research methods. The form of research is descriptive research.The research was conducted in 3 cycles. Each cycle consists of planning, implementation, observation and reflection. Research tool used in the form of tests, observation sheets, video recording learning activities, and field notes. Sources of data in this study were teachers and students. The research data in the form of findings on observations and results of evaluation of the students then treated qualitatively. The results showed that the use of visual media in learning to play musical fingering can improve the skills of the students play soprano recorders VIIB SMP Negeri 7 Sungai Raya. Such improvements can be seen from cognitive value of 3.52 (completeness 88%), being 3.37 (completeness 84%), ending 3.50 (completeness 87,5%), and value skills / practice of 2,73 (completeness 68%) to 3.02 (completeness 76%), ending with 3.24 (completeness 81%).Keywords: mastery of fingering, soprano recorders, fingering visual media.